2018
DOI: 10.1039/c8ta08900k
|View full text |Cite
|
Sign up to set email alerts
|

All-inorganic CsPbBr3 perovskite solar cell with 10.26% efficiency by spectra engineering

Abstract: Through fabricating a perovskite/photoactive layer mixed light-harvester, the all-inorganic CsPbBr3 PSC achieved a champion PCE of 10.26% and excellent stability in high humidity or high temperature atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(142 citation statements)
references
References 37 publications
1
136
0
5
Order By: Relevance
“…The VB of M-CsPbBr 3 (À5.60, À5.58, À5.61, and À5.63 eV for 0.5 %, 1%,2%, and 4%M-CsPbBr 3 ,respectively) is shiftedu pt oa pproacht he work function of carbon compared with that of the pristine perovskite(À5.66 eV), indicating ar educed energy level difference between the perovskite layer and carbon electrode, which facilitates the transportation as well as extraction of holes and reducest he loss of energy and photogenerated electrons at the interfacef or improved PCE. [36][37][38] The photocurrent-voltage (J-V)c urveso fP SCs based on CsPbBr 3 with or without melamine are measured under simulated AM 1.5G (100 mW cm À2 )s olari llumination (Figure 4c). Ta ble 1s ummarizes the photovoltaic parameters of V OC ,s hortcircuit current density (J SC ), fill factor (FF), and PCE for various devices.T he photovoltaic performance of the devices based on M-CsPbBr 3 is evidently improved, ac hampion 1%M-CsPbBr 3 -based device displays the optimal performance with a PCE of 9.65 %, J SC of 7.42 mA cm À2 , V OC of 1.584 V, andF Fo f 82.11%,y ieldingamarked improvement in comparison with the pristine CsPbBr 3 PSC (PCE:6 .07 %, J SC :5 .87 mA cm À2 , V OC : 1.401 V, and FF:7 3.80 %) and other reportedC sPbBr 3 solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…The VB of M-CsPbBr 3 (À5.60, À5.58, À5.61, and À5.63 eV for 0.5 %, 1%,2%, and 4%M-CsPbBr 3 ,respectively) is shiftedu pt oa pproacht he work function of carbon compared with that of the pristine perovskite(À5.66 eV), indicating ar educed energy level difference between the perovskite layer and carbon electrode, which facilitates the transportation as well as extraction of holes and reducest he loss of energy and photogenerated electrons at the interfacef or improved PCE. [36][37][38] The photocurrent-voltage (J-V)c urveso fP SCs based on CsPbBr 3 with or without melamine are measured under simulated AM 1.5G (100 mW cm À2 )s olari llumination (Figure 4c). Ta ble 1s ummarizes the photovoltaic parameters of V OC ,s hortcircuit current density (J SC ), fill factor (FF), and PCE for various devices.T he photovoltaic performance of the devices based on M-CsPbBr 3 is evidently improved, ac hampion 1%M-CsPbBr 3 -based device displays the optimal performance with a PCE of 9.65 %, J SC of 7.42 mA cm À2 , V OC of 1.584 V, andF Fo f 82.11%,y ieldingamarked improvement in comparison with the pristine CsPbBr 3 PSC (PCE:6 .07 %, J SC :5 .87 mA cm À2 , V OC : 1.401 V, and FF:7 3.80 %) and other reportedC sPbBr 3 solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…When the organic HTL is replaced by the inorganic HTL such as NiO x , the moisture stability can be further improved significantly. Yuan et al investigated NiO x as HTL in CsPbBr 3 solar cells and found that the devices not only showed a high PCE above 10.26% but also exhibited high stability under the conditions with a RH of 80% (Figure f) …”
Section: Stabilitymentioning
confidence: 99%
“…[124] Lau et al berichteten über die Zugabe von Ca 2+ zu CsPbI 3 (ca. [134] [15] Die gleiche Arbeitsgruppe dokumentierte auch die hçhere Stabilitätv on CsPbBr 3 im Vergleich zu MAPbBr 3 gegenüber Wärme, Elektronenbestrahlung und in Zellen. [125] In diesem Fall stieg die Korngrçße des HaP,und es wurde keine geometrische Spannung eingeführt.…”
Section: Einbau Von Ionenunclassified
“…[132,133] Im Gegensatz zu CsPbI 3 ist CsPbBr 3 in der orthorhombischen Struktur nahe Raumtemperatur stabil. [134] [77] Copyright 2018, Wiley-VCH.b)Passivierung von CsPbBr 3 -QDs mit kurzen Liganden. Abdruck mit Genehmigung.…”
Section: Gemischte 2d/3d-filmeunclassified